(untitled) - Jurkovicova, Hana (Doprava a spoje, 2012)
At present the important issue is the quality of bus stops and wheelchair access to the bus stop. This paper is an overview of the legislation in the area of the quality of public transport. The paper deals with the quality of the stops in terms of accessibility to the station. The article also prepared specifications for the design of bus stops.